Еlectrophysical parameters of the diodes for broadband noise generation - Busliuk, Viktar V.; Neroda, Ilona Y.; Pyatlitski, Aliaksandr N.; Prasalovich, Uladzislau S.; Yankouski, Yuri N. (Journal of the Belarusian State University. Physics, 2017)
The volt-ampere and volt-farad characteristics of silicon diodes – noise generators fabricated by the planar technology for the formation of small diameter (<10 mm) cylindrical p–n-junctions on the basis of the (111) orientation monocrystal silicon substrates with r = 0.03 Ohm ∙ cm (ND102 – ND104) and r = 0.005 Ohm ⋅ cm (ND 201) are analyzed. A depth of the p–n-junction formed by diffusion of phosphorus is 6 μm. On reverse switching, the breakdown voltage for all diodes is growing with the increased measuring temperature due to a decrease in the mean free path of the charge carriers. With the reverse bias possess, the volt-ampere characteristics are activation in nature. As shown by the analysis performed, in all cases the dependence is stronger than Irev U n, n ≈ 1. The activation energy of the process under study is within the range 0.25–0.45 eV. This is peculiar for thermal ionization from deep impurity centers of the technological (background) impurities such as Cu and Fe. The capacitance-voltage characteristics are insignificantly dependant on temperature pointing to the fact that the concentration of these centers in the vicinity of the p–n-junction volume charge is minor as compared with the doping level. It may be concluded that avalanche breakdown of the p–n-junction is strongly localized, microplasmic in its nature, and determined by ionization of the technological impurities which form the base of microplasmas inhomogeneously distributed over the crystal bulk.